Insights into the anaerobic digestion of fecal sludge and food waste in Tanzania - Kilucha, Malimi; Cheng, Shikun; Minza, Selele; Nasiruddin, Sayed Mohammad; Velempini, Kgosietsile; Li, Xinying; Wang, Xuemei; Mokeira Doroth, Kerage; Li, Zifu (Frontiers in Environmental Science, 2022)
With the increasing demand for renewable energy and environmental protection, biogas technology has attracted considerable attention around the world. Fecal sludge (FS) is rich in organic matter, and it contains high concentrations of excreted pathogens that cause gastro-intestinal infection. In Tanzania, fecal sludge management from on-site sanitation systems poses a threat on environmental safety. This study aimed to assess the feasibility of the use of anaerobic digestion (AD) for the treatment of FS and the production of biogas as renewable energy to achieve multiple benefits in Tanzania. For the experiments, FS and food waste (FW) were used as a feedstock, and rice straw derived biochar (RSB) was added as an additive to improve biogas production. The mesophilic anaerobic digestion resulted in a methane yield of 287.5 ml/gVS for FS+FW co-digestion and 396 ml/gVS for FS+FW+RSB co-digestion. At ambient temperature (20–26 ℃), the system produced a methane yield of 234 ml/gVS for FS+ FW co-digestion and 275 ml/gVS for FS+FW+RSB co-digestion. Three different scenarios (digester with volumes of 4, 100, and 400 m3, respectively) and strategies for FS treatment by AD in Tanzania were proposed and analyzed. These treatments can produce methane volumes of 1.95, 49.5, and 199.5 m3 with pay-back periods of 3, 5, and 15 years and net present values of +28, +1,337, and +52,351 USD, respectively. The calculations also showed that the heat value from the produced biogas and energy needed to heat the digester at 26–37 ℃) resulted in energy balance values of + 0.012, + 0.53, and +2.22 GJ/day for the 4, 100, and 400 m3 digester, respectively.